Model-mediated telehaptic perception of delayed curvature - Velanas, S. V.; Tzafestas, C. S. (2012 IEEE RO-MAN: The 21st IEEE International Symposium on Robot and Human Interactive Communication, 2012)
This paper proposes a model-mediated telemanipulation scheme, focusing on the kinaesthetic perception of specific geometric properties of the remote environment in the presence of time delay. The basic idea is inspired from previous work on impedance-reflection teleoperation, which is here extended to incorporate the construction of a two-dimensional local geometric model. This model incorporates the local curvature of the remote environment, estimated online using a recursive least squares (RLS) method, which is then used to reconstruct a virtual surface model at the master site for haptic display. A series of experiments has been conducted, where each subject manipulated the haptic master to kinaes-thetically explore the surface of a remote (virtual) environment. The analysis of the obtained experimental results, in terms of telehaptic discrimination of curvature, shows the effectiveness of the proposed model-mediated scheme at mitigating some of the adverse effects of time delay in the communication loop.